2017
DOI: 10.1093/nar/gkx734
|View full text |Cite
|
Sign up to set email alerts
|

The Rio1p ATPase hinders premature entry into translation of late pre-40S pre-ribosomal particles

Abstract: Cytoplasmic maturation of precursors to the small ribosomal subunit in yeast requires the intervention of a dozen assembly factors (AFs), the precise roles of which remain elusive. One of these is Rio1p that seems to intervene at a late step of pre-40S particle maturation. We have investigated the role played by Rio1p in the dynamic association and dissociation of AFs with and from pre-40S particles. Our results indicate that Rio1p depletion leads to the stalling of at least 4 AFs (Nob1p, Tsr1p, Pno1p/Dim2p an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
(84 reference statements)
0
23
0
Order By: Relevance
“…The sedimentation profile showed that the majority of Tsr1-FPZ pre-40S particles presented a peak position very similar to that of mature 40S ribosomal subunits, thus migrating as "free" pre-40S subunits. A smaller peak of heavier fractions indicates that Tsr1-FPZ could be found in bigger complexes, some of them probably being 80S-like particles [29,30,34,35] (Figure 1a, upper panel). Transmission electron microscopy (TEM) observations after negative staining confirmed that the particles sedimenting on lighter fractions had the overall size and shape of 40S subunits, while heavier fractions contained larger, rounder objects, with dimensions compatible with 80S-like particles (Figure 1a, lower panel).…”
Section: Proteomic Characterization Of Tsr1-purified Pre-40s Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sedimentation profile showed that the majority of Tsr1-FPZ pre-40S particles presented a peak position very similar to that of mature 40S ribosomal subunits, thus migrating as "free" pre-40S subunits. A smaller peak of heavier fractions indicates that Tsr1-FPZ could be found in bigger complexes, some of them probably being 80S-like particles [29,30,34,35] (Figure 1a, upper panel). Transmission electron microscopy (TEM) observations after negative staining confirmed that the particles sedimenting on lighter fractions had the overall size and shape of 40S subunits, while heavier fractions contained larger, rounder objects, with dimensions compatible with 80S-like particles (Figure 1a, lower panel).…”
Section: Proteomic Characterization Of Tsr1-purified Pre-40s Particlesmentioning
confidence: 99%
“…Pre-ribosomal particles were purified from a BY4742 Saccharomyces cerevisiae strain harboring a C-terminal tandem affinity purification tag on Tsr1 (Tsr1-FPZ). This FPZ tag is composed of a Flag peptide, a PreScission cleavage site and a Z domain derived from S. aureus protein A [35]. 12 L of yeast cells were grown at 30 • C on YPD medium (1% yeast extract, 1% peptone, supplemented with 2% glucose) to an optical density between 1.2 and 1.8 (600 nm), and harvested by centrifugation at 4000 rpm for 10 min at 4 • C. Pellets were washed twice with ddH2O, and flash frozen in liquid nitrogen.…”
Section: Purification Of Cytoplasmic Pre-40s Particlesmentioning
confidence: 99%
“…Rio1 is an essential aspartate kinase bound to very late cytoplasmic pre-40S subunits that have shed all bound assembly factors except Nob1 and Pno1 (Ferreira-Cerca et al, 2014;Hector et al, 2014;Turowski et al, 2014;Vanrobays et al, 2003;Widmann et al, 2012). Depletion of Rio1 or overexpression of a catalytically-inactive Rio1 mutant leads to the accumulation of 20S pre-rRNA and assembly factors in 80S-like ribosomes (Belhabich-Baumas et al, 2017;Ferreira-Cerca et al, 2014;Vanrobays et al, 2001;Widmann et al, 2012). However, the role Rio1 plays in 18S rRNA maturation and ribosome assembly remains unknown, despite its interest as a target for the development of anti-cancer drugs (Kiburu and LaRonde-LeBlanc, 2012;Kubinski et al, 2017;Mielecki et al, 2013;Read et al, 2013;Weinberg et al, 2017), and the observation that RIOK1 mutations accumulate in human cancers (TCGA Research Network:…”
Section: Introductionmentioning
confidence: 99%
“…When Rio1p enters the maturation pathway is unclear. Lack of Rio1p (Belhabich‐Baumas et al, ) or overexpression of a Rio1p dominant negative catalytic mutant (Ferreira‐Cerca, Kiburu, Thomson, LaRonde, & Hurt, ) impairs the release of Pno1p/Dim2p, Nob1p, Tsr1p, Dim1p, and Fap7p from 80S‐like particles, suggesting that Rio1p joins the maturation pathway prior to Fap7p intervention in the cytoplasm.…”
Section: Pre‐40s Particle Maturation In Saccharomyces Cerevisiaementioning
confidence: 99%